Perilaku asertif pada remaja di panti asuhan: Bagaimana peranan dukungan sosial dan konsep diri? - Fela Hadziqoh; Dyan Evita Santi; Rahma Kusumandari (INNER: Journal of Psychological Research, 2023)
Abstract This research was conducted with the aim of knowing the relationship between social support and self-concept with assertive behavior in adolescents at orphanages. This study uses a correlational quantitative method. The subjects in this study were 43 teenagers at the AlKahfi orphanage. The sampling technique uses purposive sampling. The data collection method uses a Likert scale or questionnaire model. The data analysis technique used is multiple regression analysis. According to the results of the research conducted on adolescents at the Al-Kahfi Orphanage in Palembang, the partial correlation test results obtained a score of t = 4.451 with a significance of 0.003 (p <0.05) meaning that there is a significant positive relationship between social support and assertive behavior so that social support is a predictor of assertive behavior. Keywords: Social Support, Self-Concept, Assertive Behavior, Orphanage Adolescents